2015
DOI: 10.1007/s10295-015-1611-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolic profiling reveals the key role of amino acids metabolism in the rapamycin overproduction by Streptomyces hygroscopicus

Abstract: Rapamycin is an important natural macrolide antibiotic with antifungal, immunosuppressive and anticancer activity produced by Streptomyces hygroscopicus. In this study, a mutant strain obtained by ultraviolet mutagenesis displayed higher rapamycin production capacity compared to the wild-type S. hygroscopicus ATCC 29253. To gain insights into the mechanism of rapamycin overproduction, comparative metabolic profiling between the wild-type and mutant strain was performed. A total of 86 metabolites were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The culture samples for enzyme activity analysis in vitro were harvested at the end of exponential phase (72 h) by centrifugation at 8000× g for 10 min at 4 °C. Cell pellets were washed 3 times by 100 mM Tris·HCl (pH 7.0) containing 5 mM MnSO 4 , 20 mM KCl, 2 mM DTT and 0.1 mM EDTA, and then resuspended in the same buffer [ 44 ]. Cell suspension was treated by ultrasonication for 10 min at 250 W for 5 cycles of 1 min each on ice bath.…”
Section: Methodsmentioning
confidence: 99%
“…The culture samples for enzyme activity analysis in vitro were harvested at the end of exponential phase (72 h) by centrifugation at 8000× g for 10 min at 4 °C. Cell pellets were washed 3 times by 100 mM Tris·HCl (pH 7.0) containing 5 mM MnSO 4 , 20 mM KCl, 2 mM DTT and 0.1 mM EDTA, and then resuspended in the same buffer [ 44 ]. Cell suspension was treated by ultrasonication for 10 min at 250 W for 5 cycles of 1 min each on ice bath.…”
Section: Methodsmentioning
confidence: 99%
“…ascomyceticus, so enhancing the supply of precursors is an e cient way to increase the production of this antibiotic [45]. It is well-known that the exogenous feeding of important metabolites is an effective method to increase the biosynthesis of precursors [46][47][48]. In our previous study, metabolic pro ling analysis showed that lysine (Lys), used for the synthesis of precursors pipecolic, and valine (Val), used for the synthesis of precursors methylmalonyl-CoA, were the key primary metabolites in the production of FK520 under the condition of adding resin HP20.…”
Section: Discussionmentioning
confidence: 99%
“…The final high ascomycin production strain ( S. hygroscopicus var. ascomyceticus H16) was identified using a previously reported high‐throughput screening method (B. Wang, Liu, Liu, Huang, & Wen, ). All engineered strains of Streptomyces are derivatives of S. hygroscopicus var.…”
Section: Methodsmentioning
confidence: 99%